EMpowerment of PArents in THe Intensive Care Questionnaire: Translation and Validation in Italian PICUs - Wolfler, A.; Giannini, A.; Finistrella, M.; Salvo, I.; Calderini, E.; Frasson, G.; Dall Oglio, I.; Di Furia, M.; Iuzzolino, R.; Musicco, M.; Latour, Jos (Lippincott Williams & Wilkins, 2016)
Objectives: To translate and validate the EMpowerment of PArents in THe Intensive Care questionnaire to measure parent satisfaction and experiences in Italian PICUs. Design: Prospective, multicenter study. Setting: Four medical/surgical Italian PICUs in three tertiary hospitals. Patients: Families of children, 0-16 years old, admitted to the PICUs were invited to participate. Inclusion criteria were PICU length of stay greater than 24 hours and good comprehension of Italian language by parents/guardians. Exclusion criteria were readmission within 6 months and parents of a child who died in the PICU. Interventions: Distribution, at PICU discharge, of the EMpowerment of PArents in THe Intensive Care questionnaire with 65 items divided into five domains and a six-point rating scale: 1 "certainly no" to 6 "certainly yes." Measurements and Main Results: Back and forward translations of the EMpowerment of PArents in THe Intensive Care questionnaire between Dutch (original version) and Italian languages were deployed. Cultural adaptation of the instrument was confirmed by a consultation with a representative parent group (n = 10). Totally, 150 of 190 parents (79%) participated in the study. On item level, 12 statements scored a mean below 5.0. The Cronbach's [alpha], measured for internal consistency, on domain level was between 0.67 and 0.96. Congruent validity was measured by correlating the five domains with four gold standard satisfaction measures and showed adequate correlations (rs, 0.41-0.71; p < 0.05). No significant differences occurred in the nondifferential validity testing between three children's characteristics and the domains; excepting parents with a child for a surgical and planned admission were more satisfied on information and organization issues.Conclusions: The Italian version of the EMpowerment of PArents in THe Intensive Care questionnaire has satisfactory reliability and validity estimates and seems to be appropriate for Italian PICU setting. It is an important instrument providing benchmark data to be used in the process of quality improvement toward the development of a family-centered care philosophy within Italian PICUs.